Perceived Versus Predicted Risks of Colorectal Cancer and Self‐Reported Colonoscopies by Members of Mismatch Repair Gene Mutation‐Carrying Families Who Have Declined Genetic Testing. Issue 1 (9th June 2013) - Flander, Louisa; Speirs‐Bridge, Andrew; Rutstein, Alison; Niven, Heather; Win, Aung Ko; Ait Ouakrim, Driss; Hopper, John L.; Macrae, Finlay; Keogh, Louise; Gaff, Clara; Jenkins, Mark
Abstract: People carrying germline mutations in mismatch repair genes are at high risk of colorectal cancer (CRC), yet about half of people from mutation‐carrying families decline genetic counselling and/or testing to identify mutation status. We studied the association of quantitative measures of risk perception, risk prediction and self‐reported screening colonoscopy in this elusive yet high‐risk group. The sample of 26 participants (mean age 43.1 years, 14 women) in the Australasian Colorectal Cancer Family Registry were relatives of mutation carriers; had not been diagnosed with any cancer at the time of recruitment and had declined an invitation to attend genetic counselling and/or testing. A structured elicitation protocol captured perceived CRC risk over the next 10 years. Self‐reported colonoscopy screening was elicited during a 45‐minute semi‐structured interview. Predicted 10‐year CRC risk based on age, gender, known mutation status and family history was calculated using "MMRpro." Mean perceived 10‐year risk of CRC was 31 % [95 % CI 21, 40], compared with mean predicted risk of 4 % [2, 7] ( p  < 0.001); this was independent of age and sex ( p  = 0.9). Among those reporting any medical advice and any screening colonoscopy ( n  = 18), those with higher risk perception had less frequent colonoscopy (Pearson's r  = 0.49 [0.02, 0.79]). People who decline genetic testing for CRC susceptibility mutations perceive themselves to be at substantially higher risk than they really are. Those with high perceived risk do not undertake screening colonoscopy more often than those who perceive themselves to be at average risk.